Novel CDKL5 Mutations in Czech Patients with Phenotypes of Atypical Rett Syndrome and Early-Onset Epileptic Encephalopathy - Záhoráková, D; Langová, M; Brožová, K; Laštůvková, J; Kalina, Z; Rennerová, L; Martásek, P (Folia biologica, 2016)
The X-linked CDKL5 gene, which encodes cyclin-dependent kinase-like 5 protein, has been implicated in early-onset encephalopathy and atypical Rett syndrome with early-onset seizures. The CDKL5 protein is a kinase required for neuronal development and morphogenesis, but its precise functions are still largely unexplored. Individuals with CDKL5 mutations present with severe global developmental delay, intractable epilepsy, and Rett-like features. A clear genotype-phenotype correlation has not been established due to an insufficient number of reported cases. The aim of this study was to analyse the CDKL5 gene in Czech patients with early-onset seizures and Rett-like features. We performed mutation screening in a cohort of 83 individuals using high-resolution melting analysis, DNA sequencing and multiplex ligation- dependent probe amplification. Molecular analyses revealed heterozygous pathogenic mutations in three girls with severe intellectual disability and intractable epilepsy starting at the age of two months. All three identified mutations, c.637G>A, c.902_977+29del105, and c.1757_1758delCT, are novel, thus significantly extending the growing spectrum of known pathogenic CDKL5 sequence variants. Our results support the importance of genetic testing of the CDKL5 gene in patients with early-onset epileptic encephalopathy and Rett-like features with early-onset seizures. This is the first study referring to molecular defects of CDKL5 in Czech cases.
Keywords: mutace; Epilepsy; Female; Phenotype; Rettův syndrom; ženské pohlaví; lidé; Protein Serine-Threonine Kinases; Mutation; genetická predispozice k nemoci; Genetic Predisposition to Disease; Brain Diseases; epilepsie; Male; Czech Republic; nemoci mozku; Česká republika; fenotyp; mužské pohlaví; Rett Syndrome; protein-serin-threoninkinasy; Humans